Temperature sensitivity of soil enzymes along an elevation gradient in the Peruvian Andes - Nottingham, A.T.; Turner, B.L.; Whitaker, J.; Ostle, N.; Bardgett, R.D.; Mcnamara, N.P.; Salinas Revilla, N.; Meir, P. (Springer, 2016)
Soil enzymes are catalysts of organic matter depolymerisation, which is of critical importance for ecosystem carbon (C) cycling. Better understanding of the sensitivity of enzymes to temperature will enable improved predictions of climate change impacts on soil C stocks. These impacts may be especially large in tropical montane forests, which contain large amounts of soil C. We determined the temperature sensitivity (Q₁₀) of a range of hydrolytic and oxidative enzymes involved in organic matter cycling from soils along a 1900 m elevation gradient (a 10 °C mean annual temperature gradient) of tropical montane forest in the Peruvian Andes. We investigated whether the activity (Vₘₐₓ) of selected enzymes: (i) exhibited a Q₁₀ that varied with elevation and/or soil properties; and (ii) varied among enzymes and according to the complexity of the target substrate for C-degrading enzymes. The Q₁₀ of Vₘₐₓ for β-glucosidase and β-xylanase increased with increasing elevation and declining mean annual temperature. For all other enzymes, including cellobiohydrolase, N-acetyl β-glucosaminidase and phosphomonoesterase, the Q₁₀ of Vₘₐₓ did not vary linearly with elevation. Hydrolytic enzymes that degrade more complex C compounds had a greater Q₁₀ of Vₘₐₓ, but this pattern did not apply to oxidative enzymes because phenol oxidase had the lowest Q₁₀ value of all enzymes studied here. Our findings suggest that regional differences in the temperature sensitivities of different enzyme classes may influence the terrestrial C cycle under future climate warming.
Keywords: β-glucosidase; β-xylanase; Q10 values; Soil carbon; Tropical montane forest; https://purl.org/pe-repo/ocde/ford#1.06.13